TNFR, TRAF2, NF-κB mRNA Levels of Glioblastoma Multiforme Cells Treated by Conditioned Medium of Umbilical Cord-derived Mesenchymal Stem Cells - Novi Silvia Hardiany; Yohana Yohana; Septelia Inawati Wanandi (The Prodia Education and Research Institute (PERI), 2019)
BACKGROUND: Glioblastoma multiforme (GBM) is a human malignant brain tumor which is arise from glial cells. Our previous study proved that GBM cells proliferation increased after treating by conditioned medium of umbilical cord-derived mesenchymal stem cells (CM-UCSCs). Cells proliferation is probably mediated by tumor necrosis factor (TNF)-α which could bind to membrane receptor and induce signaling pathway. Therefore, this research was intended to analyze the mRNA expression of TNF-α signaling pathway molecules on CM-treated GBM cells by measuring TNF receptor 1 and 2 (TNFR1 and TNFR2), TNFR associated factor 2 (TRAF2), nuclear factor kappa B (NF-κB) mRNA level, and TNFR2 protein level.METHODS: UCSCs and human glioblastoma T98G cells were cultured and harvested after 80% confluence. CM was prepared by growing UCSCs in serum alpha Minimum Essential Media (α-MEM) for 24 hours. Fifty percent concentration of CM-UCSCs was used to treat T98G cells for 24 hours. TNF-α level in CM-UCSC was detected using enzyme linked-immunosorbent assay (ELISA), while the expression of TNFR1, TNFR2, TRAF2 and NF-κB were detected using quantitative Reverse Transcriptase Polymerase Chain Reaction (qRT-PCR), and TNFR2 protein level was detected using sandwich ELISA.RESULTS: TNF-α level was detected in CM-UCSCs 4.4 pg/mL. Moreover, the expression of TNFR1, TNFR2, TRAF2 and NF-κB were significantly 1.4-fold, 4.9-fold, 5.6-fold, 1.8-fold respectively higher in T98G treated cells than control. TNFR2 protein level in T98G treated cells was 11.57 pg/mg protein higher than control.CONCLUSION: The expression of molecules involved in TNF-α signaling pathway were up regulated in T98G cells treated by CM-UCSCs.KEYWORDS: CM-UCSCs, TNFR1, TNFR2, TRAF2, NF-κB, T98G cells